2006
DOI: 10.1016/j.pbb.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased nicotine self-administration following prenatal exposure in female rats

Abstract: There is a significant association between maternal cigarette smoking during pregnancy and greater subsequent risk of smoking in female offspring. In animal models, prenatal nicotine exposure causes persistent alterations in cholinergic and monoaminergic systems, both of which are important for nicotine actions underlying tobacco addiction. Accordingly, the current study was conducted to determine if there is a cause-and-effect relationship between prenatal nicotine exposure and nicotine self-administration st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 43 publications
4
66
0
Order By: Relevance
“…In fact, evidence exists that prenatal nicotine increases anxiety in rodents (Huang et al, 2007;Santiago and Huffman, 2013;Vaglenova et al, 2008), although also see Amos-Kroohs et al (2013). Exposed animals are more likely to self-administer nicotine later in life (Chistyakov et al, 2010;Levin et al, 2006). Others have shown that exposed rodents are more sensitive to the rewarding (Harrod et al, 2012) and locomotor-stimulating (Amos-Kroohs et al, 2013) properties of METH.…”
Section: Tobacco/nicotinementioning
confidence: 99%
“…In fact, evidence exists that prenatal nicotine increases anxiety in rodents (Huang et al, 2007;Santiago and Huffman, 2013;Vaglenova et al, 2008), although also see Amos-Kroohs et al (2013). Exposed animals are more likely to self-administer nicotine later in life (Chistyakov et al, 2010;Levin et al, 2006). Others have shown that exposed rodents are more sensitive to the rewarding (Harrod et al, 2012) and locomotor-stimulating (Amos-Kroohs et al, 2013) properties of METH.…”
Section: Tobacco/nicotinementioning
confidence: 99%
“…Although prenatally exposed females self-administer equivalent levels of nicotine to that of controls upon initial drug exposure, they ingest significantly more following a period of abstinence (Levin et al, 2006). Furthermore, such females exhibit greater locomotor sensitization in response to cocaine challenge after a period of drug withdrawal (Franke et al, 2007).…”
Section: Behavioral Disordersmentioning
confidence: 99%
“…Experience with these preparations suggests that their use is not associated with an increased risk of chronic obstructive pulmonary disease, lung cancer or cardiovascular disease [3,11] although there are reports that nicotine may be metabolized to compounds that are potentially carcinogenic [12,13] . Furthermore, studies with experimental animals suggest that the ingestion of nicotine during pregnancy can have adverse effects on the brain development of the fetus and the vulnerability of the progeny to nicotine dependence [14,15] . Relatively little direct information is available for the effects of maternal nicotine on human development and behaviour.…”
Section: Introductionmentioning
confidence: 99%